Childfree, the Digital Era, and Islamic Law: Views of Nahdlatul Ulama, Muhammadiyah, and Gender Activists in Malang, Indonesia - Zuhriah, Erfaniah; Rahmawati, Erik Sabti; Aprilyanti, Melinda; Chaidaroh, Umi; Ch, Mufidah (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
Childfree is a life choice not to have children after or before marriage, whether biological children, stepchildren, or adopted children. This article discusses how childfree is influenced by the digital era and what the perspective of Islamic law is according to the views of ulama and gender activists in Malang, East Java. This empirical legal study used legal sociology and maqāṣid al-sharī’ah approaches. Data were collected by means of in-depth interviews and a literature review. Findings showed that child-free development in Indonesia has been influenced by the digital era through online media, which quickly spread and made it easier for people from various countries to interact and share information. One of the objectives of Islamic law (maqāṣid al-sharī'ah) is to maintain offspring (hifz al-nasl) through marriage. According to the ulama, being childfree is contrary to Islamic law and the nature of humanity. According to the Nahdlatul Ulama, Muhammadiyah, and gender activists, the laws on childfree can be summed up in two ways: haram and mubah. Childfree is haram (unlawful) because it is contrary to maqāṣid al-sharī’ah, i.e., preserving offspring, as it is also the goal of marriage. Childfree is mubah (allowed) if there are reasons that are condoned by the sharia, e.g., health problems, physical limitations, and psychological conditions that prevent the wife from having children. Sociologically, the government and all related parties need to provide education to the public so that the meaning of childfree can be understood properly and correctly.